Sistem Informasi Manajemen Asset Berbasis Web - Susanti, Esti (Jurnal Etnik: Ekonomi-Teknik, 2021)
This web-based Asset Information System is a system that provides reports on the status of goods, the number of goods, records data on the purchase of goods, makes submissions and complaints of goods, and does not discuss intangible assets or non-monetary assets that can be identified but have no substance. physical assets, Examples of intangible assets are patents, copyrights, and trademarks. Problems that occur in asset processing at PT Telkom Indonesia Tbk The Service Solution Division is currently still using a data processing system in the form of Microsoft Excel. This is less efficient in terms of time, energy, and cost. With the development of technology, it can be used to overcome some of the obstacles faced today, such as by creating a system that helps in managing assets, inventory items, and also borrowing office inventory items to prevent damage, loss, or "ghost items". Web-based system development is used with system modeling, namely UML (Unified Modeling Language), including use case diagrams, activity diagrams, sequence diagrams, and class diagrams. The asset management system development methodology uses a prototype model, PHP programming, and MYSQL database.